2001
DOI: 10.1161/hc3101.093867
|View full text |Cite
|
Sign up to set email alerts
|

Lumen Loss in Transplant Coronary Artery Disease Is a Biphasic Process Involving Early Intimal Thickening and Late Constrictive Remodeling

Abstract: Background-Coronary artery disease is the major cause of late cardiac allograft failure. However, few data exist regarding the natural history of changes in intimal and external elastic membrane (EEM) areas after heart transplantation. Methods and Results-In 38 transplant recipients, serial intravascular ultrasound examinations were performed 3.7Ϯ2.2 weeks after transplantation and annually thereafter for 5 years. In 59 coronary arteries, we compared 135 matched segments among serial studies. In each segment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…This is important because lumen loss in CAV is caused not only by intimal thickening but also by changes in external elastic membrane area. (1618) We show that the addition of a liver graft attenuates plaque progression with no effect on vessel volume progression. This suggests that the mechanism of slower progression of CAV with H+Liver Tx involves a reduced rate of intimal hyperplasia and plaque progression with no effect on vessel remodeling, at least in the first two years after transplant.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is important because lumen loss in CAV is caused not only by intimal thickening but also by changes in external elastic membrane area. (1618) We show that the addition of a liver graft attenuates plaque progression with no effect on vessel volume progression. This suggests that the mechanism of slower progression of CAV with H+Liver Tx involves a reduced rate of intimal hyperplasia and plaque progression with no effect on vessel remodeling, at least in the first two years after transplant.…”
Section: Discussionmentioning
confidence: 83%
“…3D IVUS is presently considered the gold standard for the evaluation of CAV (1416) and quantifies both intimal thickening and changes in external elastic membrane area (arterial remodeling). This is important because lumen loss in CAV is caused not only by intimal thickening but also by changes in external elastic membrane area.…”
Section: Discussionmentioning
confidence: 99%
“…In their serial 2D-IVUS study, Tsutsui et al 33 reported that early lumen loss on CAV was caused by intimal thickening, while late lumen loss was caused by vessel constriction. Our results showed that the mechanism for lumen loss in the DA group was consistent with that in Tsutsui et al's study.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated BNP has also been correlated with the development of CAV (Mehra et al, 2004b). BNP may be useful in combination with angiographic findings in predicting outcomes, with 50% of patients with high BNP levels and angiographic CAV experiencing cardiac death (Tsutsui et al, 2001). Biomarkers may hold predictive correlation, but are not used routinely for the evaluation of CAV.…”
Section: Ivus Parameters Include Intimal Thickness Intimal Index Anmentioning
confidence: 99%